2019
DOI: 10.5455/javar.2019.f344
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Escherichia coli isolated from broilers sold at live bird markets in Chattogram, Bangladesh

Abstract: Objective:The present study was carried out to appraise the antibiotic resistance and to detect some of the target resistant genes in Escherichia coli (E. coli) isolated from apparently healthy broilers.Materials and Methods:Cloacal swab samples (n = 60) were collected from apparently healthy broilers (n = 60) sold at two different live bird markets (LBMs) of Chattogram, Bangladesh. Isolation and identification of the Escherichia coli was done by the following standard bacteriological techniques followed by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 21 publications
10
34
4
Order By: Relevance
“…However, the most alarming finding from our study is that all the APEC isolates were MDR in class. Similar findings were recorded in E. coli in poultry in Bangladesh [ 30 , 70 , 71 , 72 ], though the E. coli isolates had not been characterized as APEC. Subedi et al [ 17 ] recorded 94% of APEC isolates as MDR in Nepal, similar to our findings.…”
Section: Discussionsupporting
confidence: 80%
“…However, the most alarming finding from our study is that all the APEC isolates were MDR in class. Similar findings were recorded in E. coli in poultry in Bangladesh [ 30 , 70 , 71 , 72 ], though the E. coli isolates had not been characterized as APEC. Subedi et al [ 17 ] recorded 94% of APEC isolates as MDR in Nepal, similar to our findings.…”
Section: Discussionsupporting
confidence: 80%
“…However, similar study from Bangladesh reported 100% MDR in E. coli isolates [43]. Open access between poultry farms and communities, unhygienic practice, inappropriate use of antibiotics, are some of the reasons attributed for emerging resistance patterns including MDRs in Nepal [33,43,44].…”
Section: Discussionmentioning
confidence: 98%
“…This is the first study to report the association of multidrug-resistant APEC phylotypes in avian colibacillosis in different poultry farms of Bangladesh. A likely explanation to this high level of MDR potential in pathogenic APEC isolates could be the improper disinfection management, lack of empty period of implementation between flocks, lack of knowledge about cleanliness, impure poultry feed and feeding environment, use of contaminated water, and extensive use of antimicrobials in chickens, often without veterinary prescription, as reported in many earlier studies [ 40 , 41 , 42 , 43 ]. In the present study, 392 probable APEC isolates were obtained from 130 poultry samples (droppings, cloacal, feed, handler, egg, water, liver) collected from three districts (Narsingdi, Narayangonj and Manikgonj) of Bangladesh, with 44.39% prevalence of colibacillosis.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study provided evidence that the poultry farms could indeed be contaminated with multidrug-resistant (MDR) APEC phylotypes, especially with the potentially pathogenic B2 and D2 phylotypes. This is particularly alarming for Bangladesh because of having a high disease burden, emergence of resistance traits, and the confluence of prevailing socio-economic, demographic, and environmental factors [ 40 , 41 ]. This is the first study to report the association of multidrug-resistant APEC phylotypes in avian colibacillosis in different poultry farms of Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation